PENGARUH COAL MINES (SPECIAL PROVISIONS) ACT, 2015 TERHADAP PERDAGANGAN BATUBARA INDIA – INDONESIA - Muhammad, Iqbaal; Pahlawan, Indra (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2019)
This research aims to find the effect of Coal Mines (Special Provisions), Act 2015 on coal mining industry in Indonesia. Coal Mines (Special Provisions), Act 2015 is an Act that aims to utilize coal optimally and expected to reduce dependence on imported coal.This research uses explanative research methods and literature studies as data collection techniques. The researcher uses the perspective of dependency with the nation state as a level of analysis and uses the concept of national energy policy.The results of this study shows Coal Mines (Special Provisions) Act, 2015 has a negative influence on the Indonesian coal industry such as Reliance Coal Resources which sells their coal mines in Indonesia and the volume of coal exports to India is decreased. Keywords : Act, Coal, India, Indonesia, Trade